Study on the thermoregulation of the honeybee colony: (A. mellifera) in winter - Szalai, Tamás; Loksa, Gábor; Pintér, Krisztina; Szalai, Dániel; Saláta, Dénes (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
The thermoregulation of the honeybee colony in most countries in the moderate climate is essential for the overwintering. The winter cluster can survive under hard climatic and meteorological conditions. There are many studies on the individual bee and colony behaviour, however the influence of the environment and temperature need further observations. Between 5 December and 26 February 2012/13, at Gödöllő we studied the temperature of the environment and the colony with 30 and 15 minutes frequency. During the whole period the mean temperature inside and outside the colony was 22,5 and -0,66 °C, respectively. Clear relation was found between the winter cluster- and outside temperature. Similar trends could be followed when the outside temperature rose in the colony at different intervals. Due to temperature rises or mechanical disturbances the success of overwintering may decrease. High frequency temperature recordings can help to understand the reaction and behaviour of the colonies through the environmental adaptation process.
Keywords: apiculture; colony; wintering; thermoregulation